Associations between birth weight, obesity, fat mass and lean mass in Korean adolescents: the Fifth Korea National Health and Nutrition Examination Survey - Kang, Myunggee (BMJ Open, 2018)
OBJECTIVE: Previous studies on the relationship between birth weight and obesity in adolescents have mostly been conducted within Western populations and have yielded inconsistent results. We aimed to investigate the association between birth weight, obesity, fat mass and lean mass in Korean adolescents using the fifth Korea National Health and Nutritional Examination Survey (KNHANES V). METHODS: The study population consisted of a total of 1304 (693 men and 611 women) participants aged between 12 and 18 years. Adjusted ORs and 95% CIs were calculated by multivariable logistic regression analyses to determine the association between birth weight and being overweight or obese. Furthermore, adjusted mean values for body mass index (BMI), fat mass index (FMI) and lean mass index (LMI) according to birth weight were calculated by multiple linear regression analyses. RESULTS: Individuals within the highest 25th percentile in birth weight were more likely to be overweight (adjusted OR (aOR) 1.75, 95% CI 1.11 to 2.76) compared with adolescents within the 25th and 75th percentile in birth weight. Female adolescents who were in the highest 25th percentile in birth weight were more likely to be obese (aOR 2.13, 95% CI 1.03 to 4.41) compared with those within the 25th and 75th percentile in birth weight. Increasing FMI, but not LMI was associated with increasing birth weight (P for trend: 0.03). This tendency remained only in female population in sex-stratified analysis (P for trend: 0.03). CONCLUSIONS: High birth weight may lead to obesity and increased fat mass, but not lean mass. Adolescents born with high birth weight may benefit from close weight monitoring and early intervention against obesity.